A broad analysis of resistance development in the malaria parasite - Victoria C. Corey (Nature Portfolio, 2016)
It is unclear whether new antimalarial compounds may rapidly lose effectiveness in the field because of parasite resistance. Here, Corey et al.investigate the acquisition of drug resistance and the extent to which common resistance mechanisms decrease susceptibility to a diverse set of 50 antimalarial compounds.